Uncovering the asymmetric information content of high-frequency options - Alexiou, Lykourgos; Bevilacqua, Mattia; Hizmeri, Rodrigo (Journal of Banking & Finance, 2026)
We propose option realized semivariances and signed jumps as new “observable quantities” to summarize the asymmetric information contained in the sign of high-frequency option returns. These measures successfully capture the direction of the discontinuities related to both the underlying asset and risk factor, yielding incremental information not contained in the aggregate option realized measures. Using options data on S&P 500 ETF (SPY) and 15 individual equities, we document that the negative (positive) semivariance and signed jump of out-of-the-money call (put) options play a prominent role in predicting future variance, variance risk-premia, and excess monthly returns. Out-of-sample volatility timing strategies based on these measures generate economically significant gains of up to 206 basis points annually for risk-averse investors.